Paul and Pseudepigraphy. - Porter, Stanley E. (Pauline Studies, 2013)
In Paul and Pseudepigraphy , an international group of scholars engage open questions in the study of the Apostle Paul and those documents often deemed pseudepigraphal. This volume addresses many traditional questions, including those of method and the authenticity of several canonical Pauline letters, but they also reflect a desire to think in new ways about persistent questions surrounding pseudepigraphy. The focus on pseudepigraphy in relationship to Paul affords a unique opportunity to address this innovative inclination, not readily available in studies of New Testament pseudepigraphy in general. Regarding these concerns, new approaches are introduced, traditional evidence is reassessed, and some new suggestions are offered. In addition to Pauline letters, treatments of related non-canonical Pauline pseudepigraphs are included in discussion.